Origin and ontogeny of the extrafloral nectaries associated to the inflorescences of Vigna candida and Vigna caracalla (Leguminosae, Phaseoleae) - Ojeda, Fabiana Soledad (2015)
The morphology , ontogeny and secretion of the extrafloral nectaries (EFNs) in the inflorescences of Vigna candida and Vigna caracalla were studied. The node s along the inflorescences were processed with standard techniques for light as well as scanning and transmission electron microscopy. In each node, several EFNs are formed between the flowers. The EFNs originate from flower buds that stop their growth and detach, leaving an orifice bellow which there are longitudinally enlarged cells (central cells) surrounded by a circular mound (ring). Both zones secrete. Fo u r ontogenetic stages succeed , being the third the secretory one. In each node, different EFNs are in different stages of development simultaneously , so there is always a functional nectary accompanying the flowers buds, the flowers in anthesis or the maturing fruits. Ultrastructure characteristics suggest that secretion follows the granulocrine pathwa y. The two studied species, together with Vigna adenantha, which belong to the same subgenus, share the most important characters, but differ from the corresponding ones of V igna luteola, w h ich is placed in a different subgenus, so the EFN traits support t he current classification. This is the first report about taxonomic implications of the EFNs of New World species of Vigna.